La matematización en el aprendizaje del movimiento rectilíneo en dos dimensiones con los estudiantes de primero y segundo año de bachillerato general unificado de la unidad educativa “La Providencia”. periodo enero 2017 – abril 2017 - Erazo Escudero, Ayrton Daniel (2017)
The research was made with the first a second BGU students from the “Unidad Educativa La Providencia” in Riobamba city, with emphasis in the mathematician method used by the students for developing rectilinear movement in two dimensions problems, the aim was routed to distinguish the math method applied in the institution. The research design was no experimental because of undeliberated manipulating data. The type of research was descriptive, explanatory and from field. The scientific method has contributed to the research process and for the data collection It realized objective evaluation for the first year of BGU with aspects related with vertical math and horizontal math. The test had the same problems, after that I proceeded with the students of second year of BGU. As a relevant research conclusion, it determinate that the students have better answers with the vertical math and through this way they don’t understand the presented phenomenon in the problem. The horizontal math is not frequently applied in the learning process inside the institution. In base of these results the recommendation is to make learning process with feedbacks and conclusion among the students about the benefits generated in the students who work in Physics using the horizontal math.